2020
DOI: 10.1002/adom.202000036
|View full text |Cite
|
Sign up to set email alerts
|

Energy Barriers Restrict Charge Carrier Motion in MAPI Perovskite Films

Abstract: Understanding of charge trapping processes in halide perovskites is vital to further improve performance of perovskite optoelectronic devices such as solar cells, photodetectors, and LEDs. In this work, transient photocurrent, time‐delayed collection field and transient fluorescence techniques along with numerical simulations are combined to address charge carrier trapping processes during their lateral motion in prototypical methylammonium lead iodide perovskite films formed on interdigitated electrodes. Carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…On the other hand, sample cooling, as we demonstrate, may change these transfer rates, leading to a situation when transfer of the second charge becomes much slower, or transfer of both charge carriers becomes significantly hindered at very low temperatures (see Figure 6), thus enabling observation of the charge separated state by means of time‐resolved PL and TA techniques. We have recently demonstrated that sample cooling causes dramatic photocurrent changes in conventional 3D MAPI films [ 42 ] indicating that energy barriers formed between perovskite grains play an important role in carrier migration. Thus, the presence of energy barriers between perovskite domains, which may be different for electrons and holes, is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, sample cooling, as we demonstrate, may change these transfer rates, leading to a situation when transfer of the second charge becomes much slower, or transfer of both charge carriers becomes significantly hindered at very low temperatures (see Figure 6), thus enabling observation of the charge separated state by means of time‐resolved PL and TA techniques. We have recently demonstrated that sample cooling causes dramatic photocurrent changes in conventional 3D MAPI films [ 42 ] indicating that energy barriers formed between perovskite grains play an important role in carrier migration. Thus, the presence of energy barriers between perovskite domains, which may be different for electrons and holes, is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…We also used low excitation intensity, when carrier recombination could be ignored. In these conditions, the photocurrent kinetics on a sub-microsecond time scale was mainly determined by the carrier trapping and by the hole extraction to hole transport layer (HTL) 39 . The control device with HTL shows faster photocurrent decay than that without HTL during initial ~ 50 ns due to the hole extraction (Fig.…”
Section: Passivation Effects On Photovoltaic Performancementioning
confidence: 99%
“…Acceleration of the PL decay at pulsed excitation fluencies, similar to our study, was shown to be mainly determined by the electron trapping. [21,22] Therefore, we assume that the incorporation of a small amount of Sr 2þ additives (≤0.4%) prolonging the second decay component reduces the electron trapping rate.…”
mentioning
confidence: 99%
“…We have recently demonstrated that such barriers almost completely hinder carrier motion at low temperatures and also reduce their motion rate at room temperature. [22] Therefore, to clarify the influence of Sr 2þ additives on the charge carrier recombination, we performed TDCF investigations, which are commonly used for this task, because it enables separation between recombination and other dynamic processes. [22,23] Briefly, in TDCF measurements, we excite the sample at zero electric field and apply the electric field after a variable delay and measure the total extracted charge as a function of the delay time.…”
mentioning
confidence: 99%
See 1 more Smart Citation